Barriers to healthcare and self-reported adverse outcomes for autistic adults: a cross-sectional study. Issue 2 (22nd February 2022) - Doherty, Mary; Neilson, Stuart; O'Sullivan, Jane; Carravallah, Laura; Johnson, Mona; Cullen, Walter; Shaw, Sebastian C K
Abstract : Objectives: Autistic people experience poor physical and mental health along with reduced life expectancy compared with non-autistic people. Our aim was to identify self-reported barriers to primary care access by autistic adults compared with non-autistic adults and to link these barriers to self-reported adverse health consequences. Design: Following consultation with the autistic community at an autistic conference, Autscape, we developed a self-report survey, which we administered online through social media platforms. Setting: A 52-item, international, online survey. Participants: 507 autistic adults and 157 non-autistic adults. Primary and secondary outcome measures: Self-reported barriers to accessing healthcare and associated adverse health outcomes. Results: Eighty per cent of autistic adults and 37% of non-autistic respondents reported difficulty visiting a general practitioner (GP). The highest-rated barriers by autistic adults were deciding if symptoms warrant a GP visit (72%), difficulty making appointments by telephone (62%), not feeling understood (56%), difficulty communicating with their doctor (53%) and the waiting room environment (51%). Autistic adults reported a preference for online or text-based appointment booking, facility to email in advance the reason for consultation, the first or last clinic appointment and a quiet place to wait. Self-reported adverse health outcomes experienced by autistic adults were associated with barriers to accessing healthcare. Adverse outcomes included untreated physical and mental health conditions, not attending specialist referral or screening programmes, requiring more extensive treatment or surgery due to late presentations and untreated potentially life-threatening conditions. There were no significant differences in difficulty attending, barriers experienced or adverse outcomes between formally diagnosed and self-identified autistic respondents. Conclusions: Reduction of healthcare inequalities for autistic people requires that healthcare providers understand autistic perspectives, communication needs and sensory sensitivities. Adjustments for autism-specific needs are as necessary as ramps for wheelchair users.